Piloting for the multidimensional job satisfaction instrument in the offshore work setting - Abdul Majid, Mohd Aliff; Mohamad, Siti Fatimah; Abdul Halim Lim, Sarina; Othman, Mohhidin (Academic Research Publishing Group, 2018)
This article draws upon pilot study to test the developed job satisfaction questionnaire with offshore catering employees. Changing the attention from a hypothetical work setting where job satisfaction is usually studied, this study investigated employees’ satisfaction with the offshore catering job as the employees perform their job in an isolated and confined work environment. The pilot study was employed as an impetus for a scale development dissertation in validating a bespoke job satisfaction instrument in the offshore catering context. In this small-scale study, the researchers investigated job satisfaction with a purposive sample of 37 (n=37) offshore catering employees using electronic-based survey. Subsequently, an individual debriefing was conducted with four respondents to improve the questionnaire items. The objectives of the pilot study were to evaluate the quality of the items and to identify potential challenges that might occur in the main study. The study findings are not extensively discussed; however, adequate information about the study background and sample characteristics are included. The study about job satisfaction among offshore catering employees was used to demonstrate the process. The key aspects of the pilot study including the amendment of items, challenges encountered during data collection, and modifications made to the actual study are discussed.